The Concept of Constitution in the History of Political Thought - Szlachta, Bogdan (De Gruyter, 2017)
The aim of the present volume is to discuss the notion of constitution from the perspectives of history of political thought. Its scholarly intention is to go beyond the approach concentrating on the formal understanding of constitution and bring forward more complex historical and philosophic-political interpretations. Our point of departure was the need to revive the somehow neglected distinction between the idea of constitution as an act of conscious law-giving activity and the notion of constitution conceived as the set of fundamental political rules derived from the very nature of political regime and its historical development.